A multi-dimensional composite coated positive electrode material and preparation method and application thereof

By depositing three-layer claddings of AlPO4, LiF and Al2O3 on the surface of the positive electrode material of lithium-ion batteries by atomic layer deposition method, the performance and safety problems of lithium-ion batteries under high voltage and high magnification conditions are solved, and high energy density is achieved. High power density and long cycle life effect.

CN118198304BActive Publication Date: 2025-01-03JIANGHAN UNIVERSITY +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410269453.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-11
Publication Date
2025-01-03
Estimated Expiration
2044-03-11

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials have problems such as crystal structure instability, volume changes in the cycle process, irreversible phase change, electrolyte decomposition and microcracks under high voltage and high magnification conditions, resulting in insufficient electrochemical performance and safety.

Method used

Three layers of AlPO4, LiF and Al2O3 are deposited on the surface of the positive electrode material by atomic layer deposition method. The thickness is controlled between 0.5-20nm by deposition of each layer of cladding to form a multi-dimensional composite cladding layer to improve electron ion transport. Rate, suppress side reactions and isolate the contact of the positive electrode material with the electrolyte.

Benefits of technology

It significantly improves the ion transmission rate and electron conductivity of the positive electrode material, extends the cycle life, improves the structural and thermal stability, and achieves high energy density, high power density and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004733602190000011
    Figure HDA0004733602190000011
  • Figure HDA0004733602190000012
    Figure HDA0004733602190000012
  • Figure HDA0004733602190000021
    Figure HDA0004733602190000021
Patent Text Reader

Abstract

The present invention provides a multi-dimensional composite coated positive electrode material and a preparation method thereof and its application in lithium ion batteries (LIBs). The multi-dimensional composite coated positive electrode material uses an atomic layer deposition method to deposit a first coating layer, a second coating layer and a third coating layer on the surface of a base material in sequence. The three coating layer components include AlPO4, LiF and Al2O3. The method ensures good ionic conductivity of the positive electrode material and uniform compactness of the coating, and completes accurate and uniform nano-level coating of the surface by atomic layer deposition technology (ALD); wherein the total thickness of the coating layer is 0.5-20nm. Thus, the multi-dimensional composite positive electrode material combines the optimized performance of oxides, fluorides and phosphate coatings, can not only effectively inhibit the occurrence of side reactions by fluoride coating, avoid corrosion of electrode materials and increase of surface impedance, but also can improve material stability by oxide coating and improve electron and ion transmission rate by electronic ion conductors, so as to achieve breakthroughs in energy density and power density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy materials, and in particular relates to a method for preparing a multi-dimensional composite coated positive electrode material and an application thereof in a lithium ion battery. Background Art

[0002] Lithium-ion batteries are currently widely used in mobile power supplies, electric vehicles, smart wearables and other fields. All lithium-ion batteries are composed of positive electrodes, negative electrodes, electrolytes, separators, current collectors and battery shells. The positive and negative electrodes are composed of active materials, conductive agents, adhesives, current collectors and other parts, which are responsible for the release and insertion of lithium ions during the charge and discharge process. Common positive electrodes include lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), lithium nickel oxide (LiNiO2), nickel cobalt manganese ternary (LiNi x Co y Mn z O2, x+y+z=1), the commercial negative electrode materials are mainly graphite carbon materials; the electrolyte is composed of lithium salts (such as LiPF6, LiClO4, LiFSI, etc.) and organic carbonate solvents, which play the role of transferring lithium ions; the diaphragm is in direct contact with the positive and negative electrodes to prevent short circuits and provide lithium ion transmission channels. Commercially available porous films include polyethylene (PE) and polypropylene (PP).

[0003] In order to meet market demand, lithium-ion batteries need to develop in the direction of high energy density, high power density, high safety performance, and long cycle life. However, under high voltage and high rate conditions, problems such as instability of crystal structure and volume change during the cycle process will be aggravated. Irreversible phase change, decomposition of electrolyte, dissolution of transition metal (TM), and formation of microcracks will lead to sacrifice of cycle stability and thermal stability and irreversible capacity decay, which limits its wider development. On the one hand, partially decomposed electrolyte products participate in the formation of a thick cathode electrolyte interface (CEI) film on the cathode surface, resulting in high impedance and low Coulomb efficiency. On the other hand, with the release of lattice oxygen, the phase transition from layered phase to spinel structure or rock salt phase will generate anisotropic stress inside the particles, leading to the expansion of microcracks, thereby exposing more surface area and oxygen release sites in the subsequent cycle process, accelerating violent exothermic reactions and thermal runaway. Therefore, the interfacial stability between cathode particles and electrolytes must be optimized to achieve excellent electrochemical performance and overcome safety issues.

[0004] At present, strategies such as ion doping, structural design, crystal type regulation and surface coating are considered to be effective methods to effectively reduce side reactions and improve the electrochemical performance of electrode materials. Ion doping improves the stability of the positive electrode by reducing lithium-nickel mixing and inhibiting oxygen release problems; structural design starts from the source and achieves high energy density and high stability in the form of core-shell structure or gradient structure; crystal type regulation is to make the positive electrode material single crystal, improve the tap density and compaction density while achieving better safety performance and cycle performance. However, it is worth noting that phase change occurs in the entire particle of the material, while problems such as lattice oxygen release and electrolyte corrosion occur at the positive electrode-electrolyte interface. Therefore, it is very cost-effective to design the particle surface interface structure and use surface coating to obtain high-performance lithium-ion batteries with high energy density. Common coating materials include: oxides (MgO, ZnO, Al2O3), fluorides (AlF3) and phosphates (AlPO4, CoPO4), which are widely used as coating layers to protect the surface of layered ternary positive electrodes, thereby improving the electrochemical performance of batteries. However, some materials usually have poor lithium ion conductivity or decompose, which in turn increases electrode polarization, thereby reducing rate performance, and different coatings have different mechanisms of action. Therefore, combining the advantages of different coatings and constructing a multi-dimensional composite coating on the positive electrode surface can improve the battery energy density and power density while achieving a long cycle life, which has important commercial application value. Summary of the invention

[0005] In response to the shortcomings of the prior art, the present application provides a method for preparing a multi-dimensional composite coated positive electrode material, which acts on the surface of the electrode material to achieve modification, so as to solve the technical problems of low energy density, power density and safety of existing electrode materials caused by the single optimization performance of the existing coating layer, narrow electrochemical window, and poor ionic and electronic conductivity.

[0006] In the first aspect, the present application provides a method for preparing a multi-dimensional composite coated positive electrode material, the method comprising sequentially depositing an AlPO4 coating layer, a LiF coating layer, and an Al2O3 coating layer on the surface of the positive electrode material powder by atomic layer deposition. The specific preparation method comprises the following steps:

[0007] (1) placing the positive electrode material to be coated, i.e., the first electrode material, into a reactor;

[0008] (2) A phosphorus source as a gas phase precursor of the first coating layer is introduced into the reactor to first allow the phosphorus source to be saturatedly adsorbed onto the surface of the material to be coated, and then an aluminum source as a gas phase precursor of the first coating layer is introduced to allow the aluminum source and the phosphorus source to react and deposit the product on the surface of the first electrode material to obtain a second electrode material having a first coating layer of AlPO4; the aluminum source of the gas phase precursor of the first coating layer is trimethylaluminum, and the phosphorus source is trimethyl phosphate.

[0009] (3) introducing a fluorine source as a gas-phase precursor of the second coating layer into the reactor so that it is saturatedly adsorbed onto the surface of the second electrode material to be coated, and then introducing a lithium source as a gas-phase precursor of the second coating layer so that the lithium source and the fluorine source react and the product is deposited on the surface of the second electrode material to obtain a third electrode material having a second coating layer of LiF; the lithium source as the gas-phase precursor of the second coating layer is lithium tert-butoxide, and the fluorine source is pyridine hydrofluoride.

[0010] (4) introducing an oxygen source of a gas-phase precursor of the third coating layer into the reactor so that it is saturated and adsorbed onto the surface of the third electrode material to be coated, and then introducing an aluminum source of a gas-phase precursor of the first coating layer so that the aluminum source reacts with the oxygen source and the product is deposited on the surface of the third electrode material to obtain a multi-dimensional composite coated electrode material having a third coating layer of Al2O3; the aluminum source of the gas-phase precursor of the third coating layer is trimethylaluminum, and the oxygen source is water.

[0011] After each coating layer is deposited to a specified thickness, the next coating layer is deposited.

[0012] The first coating layer, AlPO4, serves to increase the electron ion transmission rate of the material; the second coating layer, LiF, can inhibit the occurrence of side reactions and hinder the increase of interface impedance; the third coating layer, Al2O3, can isolate the direct contact between the positive electrode material and the electrolyte and improve the stability of the material in the air.

[0013] The first electrode material includes lithium nickel oxide (LiNiO2), lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), ternary material (Li[Ni x Co y Mn z ]O2), lithium iron phosphate (LiFePO4), lithium-rich materials and the like.

[0014] The coating is nano-scale atomic layer deposition, so the total thickness of the coating layer is 0.5-20nm.

[0015] The thicknesses of the AlPO4 coating layer, the LiF coating layer and the Al2O3 coating layer are the same.

[0016] In a second aspect, the present invention also provides a multi-dimensional composite coated positive electrode material, which is prepared by the method for preparing the multi-dimensional composite coated positive electrode material, and includes: a positive electrode active material and a coating layer located on the outer surface of the positive electrode active material, wherein the coating layers include an AlPO4 coating layer, a LiF coating layer, and an Al2O3 coating layer from the inside to the outside.

[0017] In a third aspect, the present invention also provides a method for preparing a positive electrode of a lithium-ion battery, the method comprising: stirring and mixing a positive electrode active material with a conductive agent, a binder and a solvent to form a positive electrode slurry, then coating the positive electrode slurry on a positive electrode collector and baking and drying to obtain a positive electrode, the method also comprising using the above method to perform three-layer atomic layer deposition coating on the surface of the positive electrode active material.

[0018] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0019] The method provided in the embodiment of the present application prepares a multi-dimensional composite coated positive electrode material through the ALD technology, and improves the comprehensive electrochemical performance of the material from the following aspects: (1) It can greatly improve the ion transfer rate and electronic conductivity of the positive electrode material, thereby improving the high voltage performance and rate performance of the material, and achieving high energy density and high power density; (2) The coating layer thickness accuracy at the nanometer level and the doping accuracy at the atomic level are achieved, and the coating layer is continuous and uniform in thickness, which can continuously play a physical protection role during the charge and discharge cycle; (3) The side reactions between the positive electrode material and the electrolyte are isolated to avoid corrosion, reduce the interface impedance and extend the cycle life; (4) The structural stability and thermal stability are improved to facilitate material storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0022] Figure 1 The LiNi before coating and after single-layer coating of AlPO4, LiF and Al2O3 in Example 1 of the present invention 0.5 Co 0.2 Mn 0.3 Transmission electron microscopy (TEM) image of O2 (NCM523); Figure 1 (a) is NCM523, Figure 1 (b) is LiF@NCM523, Figure 1 (c) is AlPO4@NCM523, Figure 1 (d) is Al2O3@NCM523.

[0023] Figure 2 The multi-dimensional composite coated LiNi in Example 1 of the present invention0.5 Co 0.2 Mn 0.3 TEM image of O2(NCM523).

[0024] Figure 3 This is the charge and discharge cycle test of NCM523 before coating, after single-layer coating of AlPO4, LiF, Al2O3, and after composite coating in Example 1 of the present invention.

[0025] Figure 4 These are CV diagrams at different scan rates of a half-cell with LCO as the positive electrode before coating in Example 2 of the present invention.

[0026] Figure 5 These are CV diagrams at different scan rates of a half-cell with LCO as the positive electrode after multi-dimensional composite coating in Example 2 of the present invention.

[0027] Figure 6 The charge and discharge cycle curves of the half-cell with LCO as the positive electrode before and after multi-dimensional composite coating in Example 2 of the present invention;

[0028] Figure 7 The impedance diagram of the half-cell with NCM811 as the positive electrode before and after multi-dimensional composite coating in Example 3 of the present invention;

[0029] Figure 8 The discharge capacity and capacity retention rate of the multi-dimensional composite coated positive electrode material obtained in Example 3 and different coating sequences;

[0030] Fig. 9 This is the surface electronic conductivity diagram of the NCM523 powder material after untreatment and UEIC treatment in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0032] Example 1

[0033] This embodiment provides a method for preparing a multi-dimensional composite coated positive electrode material, and the specific steps are as follows:

[0034] (1) Weigh 10 g of the nickel-containing ternary cathode material NCM523, with a specific surface area of ​​0.35 m 2 / g to calculate the required amount of ALD coating;

[0035] (2) Using ALD technology, AlPO4, LiF and Al2O3 were first coated on the surface of NCM523. In order to better study the different modification mechanisms of different coating layers on the positive electrode materials, single-layer coating of the above three coating layers was also performed on the surface of NCM523; the coating temperature was 200-280°C, and the total coating thickness was about 15nm. The thickness of each coating layer was controlled by adjusting the number of executions of each coating procedure in the preparation step. The thickness of each coating layer was 5nm.

[0036] Using ALD deposition equipment ("progressive" space-type ALD powder coating equipment, Soft Electric Technology Co., Ltd.), when the vacuum of the reaction chamber reaches about 0.01-10torr, the components of the atomic layer deposition system begin to be heated, and the temperature of the reaction chamber is controlled at 250°C. When the test temperature of each part of the system reaches the target temperature, the system is degassed to remove the water vapor in the chamber. The temperature of the phosphorus source precursor is heated to 80-90°C, and the temperature of the aluminum source, fluorine source, and water vapor source is maintained at 30°C (room temperature or appropriately heated). The atomic layer deposition technology includes the following steps:

[0037] First, an AlPO4 layer is applied.

[0038] Step (a), placing the base material of the first electrode, i.e. 10 g of nickel ternary positive electrode material NCM523 powder, into a reactor, and evacuating the reaction chamber until the vacuum reaches 10 -1 torr; the nitrogen flow rate is set to 20 standard milliliters per minute (sccm), the phosphorus source (trimethyl phosphate) gas is ejected in a pulsed form, and nitrogen is used as a carrier gas to flow into the reactor, and then it is left to stand for 5 seconds. During the standing process, the phosphorus source (trimethyl phosphate) is adsorbed onto the surface of the substrate material, and the unadsorbed phosphorus source (trimethyl phosphate) gas in the reactor is cleaned by nitrogen;

[0039] Step (b), ejecting the first gas-phase precursor aluminum source (trimethylaluminum) in a pulsed form, flowing into the reactor with nitrogen as a carrier gas, and then standing for 5 seconds, during which the trimethylaluminum is adsorbed onto the base material and reacts with the phosphorus source (trimethyl phosphate) adsorbed in the previous step, and the excess unadsorbed aluminum source (trimethylaluminum) gas in the reactor is purged by nitrogen;

[0040] The number of cycles of this coating layer is set to 50 times, and the film thickness grown in each cycle is about 0.9-1 angstroms, so the AlPO4 film thickness is about 5 nanometers;

[0041] Step (c) standing for 20 seconds, setting the nitrogen flow rate to 40 standard milliliters per minute (sccm), cleaning the excess trimethylaluminum vapor precursor in the reactor, and obtaining a second electrode material coated with an AlPO4 layer;

[0042] Then, a LiF layer is applied.

[0043] Step (d), placing the second electrode material, i.e., the powder coated with the AlPO4 layer, into the reactor, and evacuating the reaction chamber until the vacuum reaches 10 -1 torr; the nitrogen flow rate is set to 20 standard milliliters per minute (sccm), and the second gas-phase precursor lithium source (lithium tert-butoxide) is ejected in a pulsed form, and nitrogen is used as a carrier gas to flow into the reactor, and then it is allowed to stand for 5 seconds. During the standing process, the lithium tert-butoxide is adsorbed onto the surface of the second electrode material, and the excess unadsorbed lithium source (lithium tert-butoxide) gas in the reactor is purged by nitrogen;

[0044] Step (e), ejecting the fluorine source (pyridine hydrofluoride) gas in a pulsed form, flowing into the reactor with nitrogen as a carrier gas, and then standing for 5 seconds, during which the fluorine source (pyridine hydrofluoride) is adsorbed onto the surface of the second electrode material, and reacts with the lithium source (lithium tert-butoxide) adsorbed in the previous step, and the unadsorbed fluorine source (pyridine hydrofluoride) gas in the reactor is purged by nitrogen;

[0045] The number of cycles of this coating layer is set to 50 times, and the film thickness grown in each cycle is about 0.82-0.88 angstroms, so the LiF film thickness is about 5 nanometers;

[0046] Step (f), standing for 20 seconds, setting the nitrogen flow rate to 40 standard milliliters per minute (sccm), cleaning the excess lithium tert-butoxide vapor precursor in the reactor, and obtaining a third electrode material coated with an AlPO4 layer and a LiF layer;

[0047] Finally, an Al2O3 layer is applied.

[0048] Step (g), placing the third electrode material, i.e., the powder coated with the AlPO4 layer and the LiF layer, into the reactor, and evacuating the reaction chamber until the vacuum reaches 10 -1 torr; the nitrogen flow rate is set to 20 standard milliliters per minute (sccm), and the third gas-phase precursor aluminum source (trimethylaluminum) is ejected in a pulsed form, and nitrogen is used as a carrier gas to flow into the reactor, and then it is allowed to stand for 5 seconds. During the standing process, trimethylaluminum is adsorbed onto the surface of the third electrode material, and the excess unadsorbed trimethylaluminum gas in the reactor is purged by nitrogen;

[0049] Step (h), the oxygen source H2O gas is ejected in a pulsed form, flows into the reactor with nitrogen as a carrier gas, and then is allowed to stand for 5 seconds. During the standing process, the H2O is adsorbed onto the surface of the third electrode material and reacts with the aluminum source (trimethylaluminum) adsorbed in the previous step, and the unabsorbed H2O gas in the reactor is purged by nitrogen.

[0050] The number of cycles of this coating layer is set to 50 times, and the film thickness grown in each cycle is about 0.9-1 angstroms, so the Al2O3 film thickness is about 5 nanometers;

[0051] Step (i), standing for 20 seconds, setting the nitrogen flow rate to 40 standard milliliters per minute (sccm) to clean the excess trimethylaluminum vapor phase precursor in the reactor, thereby obtaining a composite coated positive electrode material.

[0052] In order to verify the optimal coating of the composite coating layer, the electrode material obtained in Example 1 was tested for powder conductivity under different pressures. The results are shown in Table 1. It can be seen that the powder conductivity is increased by about 7 times at most. Then, the base material (NCM523), three single-layer coated samples and the composite coated sample were photographed by transmission electron microscopy, as shown in Table 1. Figure 1 , Figure 2 As shown in the figure, we can see the obvious boundary lines between the coating layers, which proves the authenticity of the multi-dimensional composite coating. Finally, the half-cell made of the base material (NCM523), three single-layer coating samples and composite coating samples was subjected to charge and discharge cycle tests. Figure 3 As shown, after 120 cycles, the capacity retention rate of the half-cell made of the original matrix material (NCM523) was 77.13%, the capacity retention rate of the single-layer coated AlPO4 was 83.57%, the capacity retention rate of the single-layer coated LiF was 80.47%, and the capacity retention rate of the single-layer coated Al2O3 was 80.97%. After composite coating, it increased to 88.40%, and the first discharge specific capacity was also much higher than that of single-layer coating.

[0053] Table 1 Example 1 Four-probe powder conductivity test of NCM523 before coating and after composite coating

[0054] Pressure(MPa) <![CDATA[NCM523(μS cm -1 )]]> <![CDATA[Composite-coated NCM523 (μS cm -1 )]]> 5 30.18 113.51 8 47.92 184.84 10 60.17 259.07 12 74.55 387.60 14 88.21 445.85 16 106.04 508.73 18 113.83 660.94 20 129.05 928.51

[0055] Example 2

[0056] This embodiment provides a method for preparing a multi-dimensional composite coated positive electrode material, and the specific steps are as follows:

[0057] (1) Weigh 10 g of lithium cobalt oxide LCO, with a specific surface area of ​​0.18 m 2 / g to calculate the required amount of ALD coating;

[0058] (2) Lithium cobalt oxide LCO is coated with AlPO4, LiF and Al2O3 on its surface by atomic layer deposition (ALD) method. The coating temperature is 200-250°C and the total coating thickness is about 10nm. The thickness of each coating layer is controlled by adjusting the number of executions of each coating program in the preparation step. The thickness of each coating layer is about 3nm. Among them, AlPO4 is coated with 36 circles, with a thickness of about 3.6nm, then coated with 32 circles of LiF, with a thickness of about 3.2nm, and finally coated with 32 circles of Al2O3, with a thickness of about 3.2nm.

[0059] The atomic layer deposition steps in this embodiment refer to those in Embodiment 1.

[0060] The electrode material obtained in Example 2 was subjected to a powder conductivity test under different pressures. The results are shown in Table 2. It can be seen that the powder conductivity is increased by about 2 times at most. A half-cell was made and CV tests were performed at different scan rates. Figure 5 , Figure 4 As shown, through formula I p =269000n 3 / 2 ACD 1 / 2 v 1 / 2 (where I p is the current; n = 1; A is the electrode area; C is the lithium ion concentration; D is the diffusion coefficient). At the same voltage, the diffusion coefficient of the matrix material is lower. After calculation, it is found that the lithium ion diffusion coefficient D of the composite coated LCO during the charging process is 3.46×10 -12 cm -2 s -1 , higher than LCO before coating (1.35×10 -12 cm -2 s -1 ). At the same time, during the discharge process, the lithium ion diffusion coefficients of LCO before coating and composite coated LCO are 3.64×10 -13 cm -2 s -1 and 8.93×10 -13 cm -2 s -1 After composite coating, the ion diffusion rate increased by about 2.5 times. Then the charge and discharge test was carried out. Figure 6 As shown, the first discharge specific capacity is 191.8 and 192.2 mAh / g respectively. After 100 cycles, the discharge specific capacity of the original matrix material (LCO) is 132.1 mAh / g, while the LCO material after composite coating has a high capacity of 190.9 mAh / g. That is to say, after composite coating, the capacity retention rate after 100 cycles is increased from 68.87% to 99.32%.

[0061] Table 2 Example 2 Four-probe method powder conductivity test of LCO before coating and LCO after composite coating

[0062] Pressure(MPa) <![CDATA[LCO(μS cm -1 )]]> <![CDATA[Composite-coated LCO (μS cm -1 )]]> 5 1.60 2.49 8 1.82 3.82 10 1.96 4.17 12 2.03 8.16 14 3.77 7.94 16 4.15 7.58 18 5.61 14.25 20 7.94 16.31

[0063] Example 3

[0064] This embodiment provides a method for preparing a multi-dimensional composite coated positive electrode material, and the specific steps are as follows:

[0065] (1) Weigh 10g of high-nickel ternary cathode material NCM811, with a specific surface area of ​​0.28m 2 / g to calculate the required amount of ALD coating;

[0066] (2) Using ALD technology, AlPO4 was first coated on the surface of NCM811, then LiF was coated, and finally Al2O3 was coated. The coating temperature was 200-280℃, and the total coating thickness was about 20nm. In order to explore the improvement of performance by different coating layer thicknesses, we prepared a total of 6 multi-dimensional coated samples for electrochemical performance testing. The thickness of each coating layer was controlled by adjusting the number of executions of each coating program in the preparation steps. The thickness of each of the three coating layers was about 3nm. Among them, AlPO4 was coated 66 times with a thickness of about 6.6nm, then LiF was coated 66 times with a thickness of about 6.6nm, and finally Al2O3 was coated 68 times with a thickness of about 6.8nm.

[0067] The atomic layer deposition steps in this embodiment refer to those in Embodiment 1.

[0068] The electrode material obtained in Example 3 was subjected to a powder conductivity test under different pressures. The results are shown in Table 3. It can be seen that the powder conductivity is increased by about 30 times at most. A half-cell was made for impedance testing. Figure 7 As shown in the figure, the impedance decreases after modification, indicating that the composite coating improves the ion transport kinetics and enhances the interface stability. Figure 8 As shown, the order of coating AlPO4, LiF, and Al2O3 in Example 3 is changed to:

[0069] First coat Al2O3, then coat LiF and finally coat AlPO4;

[0070] First coat Al2O3, then AlPO4 and finally LiF;

[0071] First coat LiF, then coat Al2O3 and finally coat AlPO4;

[0072] First coat LiF, then coat AlPO4 and finally coat Al2O3;

[0073] First coat AlPO4, then Al2O3 and finally LiF;

[0074] Then, the discharge capacity and capacity retention rate of the multi-dimensional composite coated positive electrode materials obtained in Example 3 and in different coating sequences were tested.

[0075] AlPO4-LiF-Al2O3 (composite coating) has the best performance in terms of discharge capacity, capacity retention rate, etc., so it is the best coating order. Al2O3 is used in the outermost layer to resist the stability of the multi-dimensional composite coating positive electrode material in air and water, and LiF is used in the second layer to inhibit the occurrence of side reactions and electrolyte decomposition. AlPO4 is closest to the positive electrode material because it has the best compatibility with the positive electrode material and can improve the electronic and ionic conductivity of the material.

[0076] Table 3 Powder conductivity test of NCM811 before coating and NCM811 after composite coating by four-probe method in Example 3

[0077] Pressure(MPa) <![CDATA[NCM811(μS cm -1 )]]> <![CDATA[Composite-coated NCM811 (μS cm -1 )]]> 5 0.003 0.113 8 0.005 0.110 10 0.005 0.139 12 0.006 0.167 14 0.012 0.265 16 0.014 0.309 18 0.023 0.350 20 0.024 0.422

[0078] Comparative Example 1

[0079] This embodiment provides a method for preparing a material that is electrochemically inert but has good ionic and electronic conductivity, and the specific steps are as follows:

[0080] (1) Weigh 10 g of the nickel-containing ternary cathode material NCM523, with a specific surface area of ​​0.35 m 2 / g to calculate the required amount of ALD coating;

[0081] (2) Aluminum phosphate is coated on the surface of NCM523 by ALD technology, the coating temperature is 200-280°C, the coating thickness is 0.1-0.6nm, and the coated material is sintered at 200-400°C for 2-6 hours.

[0082] The electrode material obtained in Example 1 was subjected to a powder conductivity test under different pressures. The results are as follows: Fig. 9 As shown, it can be seen that the powder conductivity is increased by about 3-5 times.

[0083] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0084] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for preparing a multi-dimensional composite coated positive electrode material, characterized in that: The method comprises using an atomic layer deposition method to sequentially deposit an AlPO4 coating layer, a LiF coating layer, and an Al2O3 coating layer on the surface of a cathode material powder; The atomic layer deposition method comprises the following steps: (1) placing the first electrode material to be coated into a reactor; (2) introducing a phosphorus source as a vapor phase precursor of the first coating layer into the reactor, first saturating the phosphorus source onto the surface of the material to be coated, and then introducing an aluminum source as a vapor phase precursor of the first coating layer, so that the aluminum source reacts with the phosphorus source and the product is deposited on the surface of the first electrode material, thereby obtaining a second electrode material having a first coating layer of AlPO4; (3) introducing a fluorine source as a gas-phase precursor of the second coating layer into the reactor, so that it is saturated and adsorbed onto the surface of the second electrode material to be coated, and then introducing a lithium source as a gas-phase precursor of the second coating layer, so that the lithium source and the fluorine source react and the product is deposited on the surface of the second electrode material, thereby obtaining a third electrode material having a second coating layer of LiF; (4) introducing an oxygen source of the gas phase precursor of the third coating layer into the reactor so that the oxygen source is saturated and adsorbed onto the surface of the third electrode material to be coated, and then introducing an aluminum source of the gas phase precursor of the first coating layer so that the aluminum source reacts with the oxygen source and the product is deposited on the surface of the third electrode material, thereby obtaining a multi-dimensional composite coated electrode material having a third coating layer of Al2O3; After each coating layer is deposited to a specified thickness, the next coating layer is deposited.

2. The method according to claim 1, characterized in that The positive electrode materials include lithium nickel oxide (LiNiO2), lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), ternary materials (Li[Ni x Co y Mn z ]O2), lithium iron phosphate (LiFePO4), and at least one of lithium-rich materials.

3. The method according to claim 1, characterized in that The total thickness of the positive electrode material surface coating layer is 0.5-20 nm.

4. The method according to claim 1, characterized in that: The aluminum source of the gas phase precursor of the first coating layer is trimethylaluminum, and the phosphorus source is trimethyl phosphate.

5. The method according to claim 1, characterized in that The lithium source of the gas phase precursor of the second coating layer is lithium tert-butoxide, and the fluorine source is pyridine hydrofluoride.

6. The method according to claim 1, characterized in that The aluminum source of the gas phase precursor of the third coating layer is trimethylaluminum, and the oxygen source is water.

7. The method according to claim 1, characterized in that The thicknesses of the AlPO4 coating layer, the LiF coating layer and the Al2O3 coating layer are the same.

8. A multi-dimensional composite coated positive electrode material, characterized in that: The positive electrode material is prepared by the preparation method of the multi-dimensional composite coated positive electrode material according to any one of claims 1 to 7, comprising: a positive electrode active material and a coating layer located on the outer surface of the positive electrode active material, wherein the coating layer comprises an AlPO4 coating layer, a LiF coating layer, and an Al2O3 coating layer from the inside to the outside.

9. A method for preparing a positive electrode of a lithium ion battery, the method comprising: The positive electrode active material is stirred and mixed with a conductive agent, a binder and a solvent to form a positive electrode slurry, and then the positive electrode slurry is coated on a positive electrode collector and baked and dried to obtain a positive electrode, characterized in that the method also includes using the method described in any one of claims 1 to 6 to surface coat the positive electrode active material and / or the positive electrode.

Citation Information

Cited By

  • Positive pole piece, preparation method thereof and lithium ion battery

    CN120690805A